Influence of Work Discipline and Work Motivation Analysis on Increasing Employee Performance - Herman Sjahruddin; Fitriyana Fitriyana; Pandu Adi Cakranegara; Suryani Suryani; Abdurohim Abdurohim (Quantitative Economics and Management Studies, 2023)
The purpose of this study was to analyze the influence of work discipline and work motivation on increasing employee performance in a fish canning company in East Java. The research design used in this study used quantitative associative methods. Based on the results of data analysis that has been carried out on the first hypothesis (H1) which states that work discipline has a positive and significant effect on increasing employee performance, the t-count value is 12.303 which is greater than the t-table value of 1.692, testing the second hypothesis (H2) which states that work motivation has a positive and significant effect on increasing employee performance, the t-count value is 9.919, which is greater than the t-table value of 1.692, which means that work discipline and work motivation have a positive and significant effect on increasing employee performance, while the R-square value obtained is 0.815 which states that the work discipline and work motivation variables affect increasing employee performance by 81.50% and the remaining 18.50% is influenced by other variables.